Body Status and Occupational Health Hazards of Female Workers : A Comparative Analysis - Arora, Dimpal; Sitholay, Pooja; Sau, Soudeep Kr (International Journal of Occupational Safety and Health, 2015)
Objective: Health is nothing but a state of complete physical, mental and social wellbeing not merely the absence of disease. Health depends on life style and requires the promotion of healthy life style. Health is both a consequence of an individual’s life style and factors in determining it. Working pattern or type of work has long been known to influence human health specially. The present study was under taken to evaluate the body status and physiological stress and occupational health hazards of the female workers. Methods: According to the work load the working group was classified in to low physical work group (LPWG) and the moderate type of physical work group (MPWG). Eighty women (forty in each group), excluding pregnant women, were selected from the municipal area of Bhilai, Chhattisgarh, India, aged between 20 to 40 years. The anthropometric measurement and skin fold thickness were taken, from which the body mass index (BMI) and fat percentage were determined. The blood pressure of all the subjects was taken by mercury sphygmomanometer at resting condition. The occupational health hazards were determined by questionnaire technique. Result: The result indicates that the MPWG workers suffer in significantly (p<0.001) low weight, BMI and Fat% than that of the LPWG workers. The MPWG workers also suffer from significantly (p<0.001) higher percentage of musculoskeletal disorder (MSD) at neck, shoulder, elbow, wrist, finger, cuff and feet-ankle joint. MPWG workers, hemoglobin concentration also significantly (p<0.01) lower than that of the LPWG workers. Conclusion: It may be concluded that, this study is helpful to identify the risk factor for the occurrence of different cardiovascular as well as musculoskeletal abnormalities and accordingly prevention program, regarding proper food habit be undertaken. DOI: http://dx.doi.org/10.3126/ijosh.v4i1.12166